The peace project: creating elementary school peace spaces and places - McIntyre Miller, Whitney; Abdou, Annmary S.; Clancy, Cristie Suzukawa; Stephens, Kelly (Frontiers in Education, 2024)
This pilot case study paper demonstrates how school programming can be aligned and enhanced to better create a climate of peace on an elementary school campus by utilizing an integral peace leadership lens. Working collectively as a Peace Leadership Advisory Group, the elementary school leadership team, and the university research team helped to align existing programming and explore and implement new programming to create a comprehensive plan for bringing peace ideas together at the elementary school level. Observational data, surveys, and interviews with school leadership demonstrated that the efforts to build peace on campus were successful overall, with students and staff having a positive experience with peace programming throughout the academic year. The findings indicate that aligning existing programming as a way to frame a culture of peace and then supplementing that programming with additional activities serves as a way to unite a campus around the idea of peace.